Wong Ndhuwur, Wong Ngisor: Local Community and Post-disaster Tourism in Kinahrejo - Jordyna Austine Xaviera Susanto; Wiwik Sushartami (Humaniora, 2020)
This research has two objectives. First, it aims to determine the perspective of the local community towards the commodification of disaster tourism in Kinahrejo, one year following the 2010 eruption of Mount Merapi. Second, it aims to identify the implication of the local community’s involvement in the new tourism activities. Referring to the indicators of residents’ perceptions of involvement in post-disaster tourism development (Wright, 2014), semi-structured interviews of seven informants were conducted and several more casual conversations were held with a larger group. Two types of responses from the local community were indicated based on the respondents’ varying involvement in tourism activities. On one hand, members of the local community who benefit from employment in tourism activities have positive perspectives towards the commodification of disaster tourism in Kinahrejo. On the other hand, those who do not participate in tourism activities regard it negatively as it is not beneficial to them. Another important finding shows that the variation in involvement in the new tourism activities has caused a split in the community into two groups, namely wong ndhuwur and wong ngisor.